DEVELOPMENT OF IPAS TEACHING MATERIALS IN THE INDEPENDENT CURRICULUM FOR GRADE IV ELEMENTARY SCHOOL BASED ON METACOGNITIVE STRATEGIES - Jumanto Jumanto; Mukhlis Mustofa (Universitas Majalengka, 2023)
Metacognition is one-factor influencing students' processes and learning achievement. Many studies have shown that metacognition helps individuals become more effective learners, enabling them to regulate and improve their thinking and learning methods more effectively. This study aims to produce metacognitive-based teaching materials for the subject of Science in Grade IV Elementary School with the Merdeka Curriculum and to test its validity. This research is a Research and Development (R & D) using the Borg and Gall development model, which is simplified into seven stages: a preliminary study, research planning, design development, limited trial, revision of limited trial, large-scale trial, and revision of large-scale trial. The samples were selected using a purposive sampling technique, with 10 students in the limited trial and 26 in the large-scale trial. The validity of the teaching materials was evaluated by subject matter experts, metacognitive experts, and educational media experts, as well as response questionnaires from teachers and students. The data analysis technique used is descriptive, which presents the product development results. The results of the study show that the development of metacognitive-based teaching materials for the subject of Science in Grade IV Elementary School with the Merdeka Curriculum is valid and feasible to use, based on the validation results from subject matter experts, metacognitive experts, and educational media experts, as well as student assessment questionnaires with average criteria of excellent. The results of the large-scale trial show an increase in student learning motivation, from 45% of students with high self-directed learning motivation to 70% of 26 students. Metakognisi adalah salah satu faktor yang mempengaruhi proses dan prestasi belajar siswa. Banyak penelitian yang membuktikan bahwa metakognisi membantu seseorang menjadi pembelajar yang lebih efektif, karena metakognisi menjadikan seseorang mampu mengatur dan memperbaiki cara berpikir dan belajarnya secara lebih efektif. Penelitian ini bertujuan untuk menghasilkan bahan ajar yang berbasis metakognitif pada mata pelajaran IPAS kelas IV SD dengan Kurikulum Merdeka serta menguji kevalidannya. Jenis penelitian ini adalah Research and Development (R & D) dengan model pengembangan Borg and Gall yang disederhanakan menjadi tujuh tahap yaitu, studi pendahuluan, perencanaan penelitian, pengembangan desain, uji coba terbatas, revisi uji coba terbatas, uji coba skala luas, revisi hasil uji coba secara luas. Pengambilan sampel dilakukan dengan teknik purposive sampling yaitu 10 pesera didik pada uji coba skala terbatas dan 26 siswa pada uji coba skala luas. Validitas bahan ajar diupayakan melalui validasi ahli materi, ahli metakognitif, dan ahli media pendidikan, serta angket respon dari pendidik dan siswa. Teknik analisis data menggunakan teknik deskriptif yang memaparkan hasil pengembangan produk. Hasil penelitian menunjukkan bahwa pengembangan bahan ajar berbasis metakognitif pada mata pelajaran IPAS kelas IV SD dengan Kurikulum Merdeka valid dan layak digunakan berdasarkan hasil validasi dari ahli materi, ahli metakognisi dan ahli media serta berdasarkan angket penilaian siswa dengan rata-rata kriteria sangat baik. Hasil ujicoba skala luas menunjukkan peningkatan motivasi belajar siswa yaitu dari 45% siswa yang mempunyai motivasi belajar mandiri tinggi meningkat menjadi 70% dari 26 siswa.